PENGARUH ETIKA KERJA ISLAM DAN BUDAYA ORGANISASI ISLAM TERHADAP KINERJA KARYAWAN (Studi Pada Pegawai KSPPS Binama Semarang) - Ahnaf Fadhlurrohman; Fuad Mas’ud (Faculty of Economics and Business Diponegoro University, 2022)
This study aims to analyze the effect of Islamic work ethics and Islamic organizational culture on employee performance. This study uses Islamic work ethics and Islamic organizational culture as independent variables, and employee performance as the dependent variable. Population target in this study were employees of KSPPS Binama Semarang who had worked for more than one year and were permanent employees totaling 139 people. This study uses a non-probability method with the type of purposive sampling. Data obtained from questionnaires were processed and analyzed using the SPSS program. The data analysis method used is Multiple Regression Analysis, then the classical assumption test is carried out. Hypothesis testing using F statistical testing, t-test, and coefficient of determination test with a significance level of 5%. The results showed that Islamic work ethics and Islamic organizational culture had a positive effect on employee performance. The value of Adjusted R square shows that the variables of Islamic work ethic and Islamic organizational culture can explain employee performance variables by 80.4%. While the remaining 19.6% is explained by other factors